Effect of induced hyperopia on fall risk and Fourier transformation of postural sway - Moon, Byeong-Yeon (PeerJ, 2019)
BACKGROUND AND PURPOSE: Fall accidents are a social challenge in Korea and elsewhere. Most previous studies have focused on the effects of reduced visual acuity due to myopia on falls and body balance. The objective of this study was to investigate whether uncorrected hyperopia was a major risk factor for falls and to establish whether the risk of falls was absolutely correlated with visual acuity. METHODS: Fifty-one young subjects with a mean age of 22.75 ± 2.13 years were enrolled in this study. To induce hyperopic and myopic refractive errors, spherical lenses of ±1.0–6.0 D (1.0 D stepwise) were used. Under each induced condition, fall risk index and sway power were assessed via Fourier transformation of postural sway using a TETRAX system. RESULTS: The fall risk index for eyes-closed was significantly greater than that of eyes-open with full correction (t = −5.876, p < 0.05). The fall risk index increased significantly from hyperopia induced with −4.0 D lenses (with visual acuity of 0.69 ± 0.32) compared to eyes-open with full correction (F = 3.213, p < 0.05). However, there was no significant change in the induced myopia conditions, despite a drastic decline in decimal visual acuity. Sway power increased significantly in the low-to-medium frequency band derived from the peripheral vestibular system when hyperopia was induced. A significant difference was detected in hyperopia induced with −6.0 D lenses compared to eyes-open with full correction (F = 4.981, p = 0.017). CONCLUSION: An uncorrected hyperopia rather than myopia may increase the risk of falls, although eyes may show normal visual acuity due to the inherent accommodation mechanism. Our findings suggest that the corrected state of refractive errors is more important than the level of visual acuity as the criteria for appropriate visual input, which contributes to stable posture. Therefore, clinicians should consider the refractive condition, especially the characteristics of hyperopia, when analyzing body balance, and appropriate correction of uncorrected hyperopia to prevent falls.